Corticotropin releasing hormone (CRH) promoter polymorphisms in various ethnic groups of patients with rheumatoid arthritis. - Baerwald, C; Mok, C; Tickly, M; Lau, C; Wordsworth, B; Ollier, B; Panayi, G; Lanchbury, J (2000)
The regulatory region of the corticotropin releasing hormone (CRH) is highly conserved and plays a crucial role in the response of the organism to stress. Release of CRH initiates a cascade of events leading to the release of cortisone and the regulation of inflammatory and immune events. OBJECTIVE: Since it has been postulated that the impaired corticotropin releasing hormone (CRH) response to stress in patients with rheumatoid arthritis (RA) has a genetic basis, we investigated the distribution of CRH alleles in a cohort of UK patients as well as in South African RA patients. METHODS: Restriction fragment length polymorphism of PCR amplified DNA products of the CRH promoter. We compared the allele frequencies in the RA patients with the respective healthy control population described previously. RESULTS: As in the control populations we found two biallelic polymorphic sequences (named A1 and A2 and B1 and B2, respectively) in the CRH promoter which could be assigned to compound alleles. The A2B1 compound allele was protective against development of RA in a large group of UK Caucasoid patients (p = 0.03; odds ratio 0.43, 95% confidence interval 0.21-0.88). In contrast, A1B1 was positively associated with RA in a cohort of black South African RA patients (p = 0.05; odds ratio 1.78, 95% confidence interval 1.01-3.15). CONCLUSION: Taken together, these findings support the hypothesis that CRH promoter polymorphism represents a new genetic marker for RA susceptibility and may prove useful for the prediction of RA risk in the future when further genetic and environmental risk factors are determined.